A COMPARISM BETWEEN A FENTANYLE ALONE OR FENTANYLE AND PROPOFOL IN CONSCIOUS SEDATION IN EYE SURGERY UNDER REGIONAL ANAESTHESIA (World Bulletin of Public Health, 2023)
Regional anesthesia is popular and offers several benefits to the patient and anesthetist. Sedation is part of the general management of a patient receiving a regional block and being awake during the whole surgical procedure.